Shocks to Hospital Occupancy and Mortality: Evidence from the 2009 H1N1 Pandemic - Gutierrez, Emilio; Rubli, Adrian (Management Science, 2021)
Existing literature suggests that hospital occupancy matters for quality of care, as measured by various patient outcomes. However, estimating the causal effect of increased hospital busyness on in-hospital mortality remains an elusive task due to statistical power challenges and the difficulty in separating shocks to occupancy from changes in patient composition. Using data from a large public hospital system in Mexico, we estimate the impact of congestion on in-hospital mortality by exploiting the shock in hospitalizations induced by the 2009 H1N1 pandemic, instrumenting hospital admissions due to acute respiratory infections (ARIs) with measures of ARI cases at nearby healthcare facilities as a proxy for the size of the local outbreak. Our instrumental-variables estimates show that a 1% increase in ARI admissions in 2009 led to a 0.25% increase in non-ARI in-hospital mortality. We show that these effects are nonlinear in the size of the local outbreak, consistent with the existence of tipping points. We further show that effects are concentrated at hospitals with limited infrastructure, suggesting that supply-side policies that improve patient assignment across hospitals and strategically increase hospital capacity could mitigate some of the negative impacts. We discuss managerial implications, suggesting that up to 25%–30% of our estimated deaths at small and non-intensive-care-unit hospitals could have been averted by reallocating patients to reduce congestion. This paper was accepted by Carri Chan, healthcare management.